2006
DOI: 10.1242/jcs.02716
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase L1 regulates the morphology of neural progenitor cells and modulates their differentiation

Abstract: Ubiquitin C-terminal hydrolase L1 (UCH-L1) is a component of the ubiquitin system, which has a fundamental role in regulating various biological activities. However, the functional role of the ubiquitin system in neurogenesis is not known. Here we show that UCH-L1 regulates the morphology of neural progenitor cells (NPCs) and mediates neurogenesis. UCH-L1 was expressed in cultured NPCs as well as in embryonic brain. Its expression pattern in the ventricular zone (VZ) changed between embryonic day (E) 14 and E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 47 publications
(43 reference statements)
5
75
0
1
Order By: Relevance
“…11,40 In addition, UCH-L1 stabilizes the level of monoubiquitin by direct binding to monoubiquitin in neurons. 13,41 In the present study, UCH-L1 overexpression and knock-down in cultured podocytes resulted in higher and lower monoubiquitin levels, respectively. In rats, inhibition of UCH-L1 hydrolase activity lowered glomerular monoubiquitin in PHN and normal rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…11,40 In addition, UCH-L1 stabilizes the level of monoubiquitin by direct binding to monoubiquitin in neurons. 13,41 In the present study, UCH-L1 overexpression and knock-down in cultured podocytes resulted in higher and lower monoubiquitin levels, respectively. In rats, inhibition of UCH-L1 hydrolase activity lowered glomerular monoubiquitin in PHN and normal rats.…”
Section: Discussionsupporting
confidence: 51%
“…11 Biochemically, UCH isoforms process precursors of free ubiquitin and recycle ubiquitin from degraded substrates. 12 Several biological effects of UCH-L1 are based on its ability to bind to and stabilize monoubiquitin 13 and to perform ubiquitin ligase activity at Lys63. 14 UCH-L1 is associated with neurodegenerative disorders such as Parkinson's and Alzheimer's diseases.…”
mentioning
confidence: 99%
“…Also, targeted mutation of UBR1 and UBR2, encoding two E3 ubiquitin ligases in the N-end rule pathway, causes severe impairment of neurogenesis . Furthermore, ubiquitin C-terminal hydrolase L1 influences the morphology of neural progenitor cells and modulates their differentiation (Sakurai et al 2006). In this study, we present evidence that Trim11 could repress Pax6-dependent neurogenesis in primary cortical cultures as well as in vivo in the developing cortex by mediating Pax6 degradation via the UPS.…”
Section: Discussionmentioning
confidence: 66%
“…Ubiquitination analysis indeed showed that UCHL1 promoted the deubiquitination of p14 ARF and p53 and, meanwhile, the ubiquitination of MDM2, thus elucidating the molecular mechanism of the activation of p53 signaling by UCHL1. However, whether UCHL1 mediate these effects through its two opposite enzymatic activities (50), E3 ligase and hydrolase activity, needs to be explored further. Our results also revealed another mechanism of UCHL1 acting as a tumor suppressor gene, that is, through the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%